2012
DOI: 10.1084/jem.20120822
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 distinguishes natural and inducible regulatory T cells among regulatory T cell subsets in vivo

Abstract: Neuropilin-1 is identified as a surface marker to distinguish different Foxp3+ T reg cell subsets under homeostatic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
485
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 567 publications
(513 citation statements)
references
References 33 publications
27
485
0
1
Order By: Relevance
“…Up to now, no solid marker to discriminate thymus-derived and peripherally induced Tregs was found. Recently, Nrp-1 was proposed to be expressed at high levels on thymus-derived opposed to peripherally induced Tregs (40,41). In this study, we found lower H2BeGFP levels in Nrp1 high compared with Nrp1 low Tregs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Up to now, no solid marker to discriminate thymus-derived and peripherally induced Tregs was found. Recently, Nrp-1 was proposed to be expressed at high levels on thymus-derived opposed to peripherally induced Tregs (40,41). In this study, we found lower H2BeGFP levels in Nrp1 high compared with Nrp1 low Tregs.…”
Section: Discussionsupporting
confidence: 58%
“…Next, we sought to investigate the proliferation history of Treg populations defined by Treg-specific markers. The transcription factor Helios (39) and the surface molecule Nrp1 (40,41) were recently proposed to discriminate thymic-derived and peripherally induced Tregs. As revealed by H2BeGFP levels of the respective Treg populations in secondary lymphoid organs, Helios + and Nrp1 high Tregs had proliferated more than Helios 2 or Nrp1 low Tregs (Fig.…”
Section: Proliferation History Of Peripheral Treg Subsetsmentioning
confidence: 99%
“…This suggests that the overwhelming majority of thymus-derived, natural Treg cells express Nrp-1. 27 Similarly, Helios provides an additional marker for the discrimination of nTreg cells from iTreg cells, although its specificity remains a concern. 28,29 Nrp-1 also identifies Foxp3 1 cell stability because Nrp-1 1 nTreg cells are more stable compared with Nrp-1 2 nTreg cells.…”
Section: Foxp3 and Treg Cell Subsetsmentioning
confidence: 99%
“…In mice, CD304 expression differentiates natural (CD304 + ), from inducible (CD304 -), T reg cells [22]. While a similar distinction has yet to be reported in humans, it is pertinent to note that the bulk of …”
Section: Hcv_g1_p7_794 Suppresses the Mitogenic Response Of T Cells Tmentioning
confidence: 83%
“…This finding indicates that HCV_G1_p7_794 induces the conversion of conventional CD4 + FoxP3 -T cells to T reg cells, i.e., infectious tolerance, a suggestion supported by studies demonstrating the inability of nT reg cells to proliferate in response to their cognate antigen in vitro [34]. Furthermore, in contrast to Ab + VL + PBMCs cultured in medium alone, only a minority of CD3 + CD4 + FoxP3 + cells cultured in the presence of HCV_G1_p7_794 expressed CD304 (neuropilin), which is expressed by a subset of FoxP3 + T reg cells in humans and associated specifically with nT reg cells in mice [21,22]. While it has been suggested alternatively that the expanded T reg cell population in chronic, HCV infected patients is composed of cells phenotypically similar to nT reg or iT reg cells [11,20], our results concur with the consensus that the expanded T reg cell population in chronic HCV-infected patients is heterogeneous, composed of both T reg cell subsets.…”
Section: Discussionmentioning
confidence: 98%